2023
DOI: 10.1007/s10592-023-01570-x
|View full text |Cite
|
Sign up to set email alerts
|

Introgressive hybridization levels of Tilapiine species in Lake Victoria basin, Kenya inferred from microsatellite and mitochondrial DNA genotyping based on next-generation sequencing

Gerald Kwikiriza,
Thapasya Vijayan,
Papius Dias Tibihika
et al.

Abstract: Despite their high abundance and species richness, tilapiines have been compromised by various factors especially overfishing, climate change, and uncontrolled fish transfers and introductions. Fish introductions have negatively impacted native tilapiine populations through competition, predation, hybridization, and introgression compromising their genetic integrity. The hybridization levels of different tilapiines in the Lake Victoria basin remain relatively understudied. The study utilized nuclear microsatel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The measured levels of haplotype and nucleotide diversities among Manyara tilapia (O. amphimelas) populations were low compared to levels reported in Nile tilapia from other inland ecosystems in East Africa (Angienda et al, 2011;Kwikiriza et al, 2024;Mbilinyi et al, 2023). The low haplotype and nucleotide diversities observed among Manyara tilapia populations in SRVLs could be attributed to the semi-arid nature of the regions where these lakes are located.…”
Section: Nonetheless the Observed Absence Of Mitochondrial Introgressionmentioning
confidence: 60%
See 1 more Smart Citation
“…The measured levels of haplotype and nucleotide diversities among Manyara tilapia (O. amphimelas) populations were low compared to levels reported in Nile tilapia from other inland ecosystems in East Africa (Angienda et al, 2011;Kwikiriza et al, 2024;Mbilinyi et al, 2023). The low haplotype and nucleotide diversities observed among Manyara tilapia populations in SRVLs could be attributed to the semi-arid nature of the regions where these lakes are located.…”
Section: Nonetheless the Observed Absence Of Mitochondrial Introgressionmentioning
confidence: 60%
“…They found that the lakes were separated by approximately 10 km of wetland and papyrus swamps, creating physical barriers between them. Similarly, Kwikiriza et al (2024) observed limited genetic connectivity between populations of blue spotted tilapia (O. leucostictus) in Lake Victoria and Lake Sare, which they attributed to physical isolation caused by a main road and Yala swamp separating the two water bodies. The limited genetic connectivity between Manyara tilapia in Lake Manyara and other SRVLs is likely due to physical isolation between the lake and other SRVLs.…”
Section: Nonetheless the Observed Absence Of Mitochondrial Introgressionmentioning
confidence: 99%
“…Between 1961 and 1964, unusually high lake levels brought on by a lot of rain made it easier for tilapias to establish themselves (Nassali et al., 2020). The introduction of O. niloticus endangered the native tilapiine species through interspecific competition, hybridization and genetic swamping (Kwikiriza et al., 2023). Currently, O. niloticus predominates the majority of fish landings, whereas other tilapiine species are rarely fished (Wasonga et al., 2017).…”
Section: Resultsmentioning
confidence: 99%